IMPLEMENTASI PROGRAM PELITA EMAS DALAM MENINGKATKAN LITERASI MASYARAKAT DESA SLOGORETNO - Nadhiroh, Nadhiroh; Faiz, Achmad Zaky; Agustini, Dewi; Maskuri, M.Ibnu Naufal (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
Existing literacy programs are often partial and rely on external funding, rather than the village's internal potential. While some villages tend to prioritize physical development, Slogoretno Village prioritizes human resource development through literacy. This effort aims to ensure the community understands village programs and receives comprehensive information, not just through word of mouth. This raises the need to analyze the effectiveness of an integrated and sustainable literacy model. This study aims to analyze the comprehensive implementation of the PELITA EMAS (Literacy Education and Community Education) Program in improving community literacy in Slogoretno Village. Specifically, this study aims to analyze how literacy innovations are disseminated and accepted using the Diffusion of Innovation Theory framework. The analysis uses the Diffusion of Innovation Theory (Everett Rogers), focusing on five innovation attributes (relative advantage, compatibility, etc.) and the role of communication channels. The method used is qualitative. Data were collected through interviews and observations with the Village Fund implementation team and the community as innovation adopters.The research results show that PELITA EMAS has successfully disseminated four main literacy innovations: Science Literacy (cocoa grafting training to produce superior seeds), Financial Literacy (early savings training for PAUD and MSME management), Digital Literacy (socialization of Digital Population Identity/IKD), and Reading Literacy (development of digital libraries and TPA/TPQ). The successful adoption was driven by clear relative benefits for the community (for example, superior cocoa and ease of IKD) as well as the role of effective Interpersonal Communication Channels from external parties such as the presence of KPM/KKN students.